ANALISIS PENGARUH NIM, BOPO, LDR, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN DENGAN MODAL INTELEKTUAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budianto, Budianto (Universitas Sari Mutiara Indonesia, 2021)
The purpose of this study was to simultaneously and partially analyze the influence of NIM, BOPO, LDR, leverage and company size on the financial performance of the banking companies in the Indonesia Stock Exchange with modal intellectual as moderating variable and also to analyze the influence of modal intellectual in moderating the relationship between NIM, BOPO, LDR, leverage and company size on the financial performance of the banking companies in the Indonesian stock exchange. The population of this study was all of the 32 banking companies listed/ registered in the Indonesia Stock Exchange during the period of 2014-2018. Twenty four (26) banks were selected to be the samples for this study through purposive sampling method with 120 observations. The data obtained were analyzed through multiple linear regression analysis and residual analysis. The data used in this study were the secondary data in the form of financial reports of the banking companies listed in the Indonesia Stock Exchange during the period 2010-2014. The results of hypothesis test showed that simultaneously NIM, BOPO, LDR, leverage and company size had significant influence on the financial performance of banking companies (ROA) and also partially NIM, BOPO, LDR, company size that had significant influence on the financial performance of banking companies (ROA) but only leverage did have in significant influence on the financial performance. The result of this study also showed that modal intellectul as moderating variable have influence significant.